A Quality Improvement Initiative Reduces Cast Complications in a Pediatric Hospital. Issue 2 (February 2018) - Balch Samora, Julie; Samora, Walter P.; Dolan, Kevin; Klingele, Kevin E.
Abstract : Background: Casts, while frequently used as routine treatment in pediatric orthopaedic practice, are not without complications. At our large tertiary care pediatric hospital, the baseline rate of all casting complications was 5.6 complications per 1000 casts applied (0.56%). We tested the hypothesis that we could use quality improvement (QI) methodology to decrease the overall cast complication rate and improve patient care. Methods: We initiated a QI program implementing concepts derived from the Institute for Healthcare Improvement models, including Plan-Do-Study-Act cycles, to decrease our cast complication rate. A resident casting education program was developed with a competency "checklist" to ensure that casts are applied, bivalved, and removed in a safe and standardized manner to prevent patient harm. AquaCast Saw Stop Protective Strips were required to be applied with every cast application. A review of our facility's processes and procedures determined adequate measures were in place to effectively manage inventory and maintenance of cast-saw blades. Results: With the multimodal QI intervention, our cast complication rate was reduced to 1.61 complications per 1000 applications, a >90% improvement. Conclusions: Implementation of QI concepts to perform a QI initiative resulted in a shift toward fewer cast complications, leading to overall improved patient care at a large tertiary pediatric hospital. Level of Evidence: Level II—prospective cohort study.